PROFIL SIKAP ILMIAH PESERTA DIDIK DALAM PEMBELAJARAN BIOLOGI OLEH CALON GURU PROGRAM PPG-SM3T DI SMA MUHAMMADIYAH 1 PEKANBARU TAHUN AJARAN 2015/2016 - Rabia Hidayanti Arnan; Yustina '; Yuslim Fauziah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purpose of this study is to describe scientific attitude of students on biology subject participants by teachers candidates PPG-SM3T at state Senior High School in Muhammadiyah 1 Pekanbaru academic year 2015/2016. This study was conducted in Oktober 2015 until Maret 2016. Instruments that used is classroom observation sheets and enclosed questionnaire. Observed scientific attitude is composed of five indicators, curiosity, cooperation, responsibility, dicipline, and conscientious. Observation sheets filled based on descriptions that have been determined. Questionnaire consists of 16 statements. All the items of enclosed questionnaire is valid and reliable, the reliability coefficient using alpha Cronbach of 0,821 Samples in this study were 106 students who are taught by teacher candidates PPG-SM3T program at state Senior High School in Muhammadiyah 1 Pekanbaru. Data that have been collected analyse by descriptive. The results of the data’s analysis showed that the scientific attitude of students who are taught by a teacher candidates PPG-SM3T program at state Senior High School in Muhammadiyah 1 Pekanbaru categorized “good” by average 82,86% based on observations and 80,74% based on questionnaires. This suggests that the scientific attitude of students who are taught by a teacher candidates PPG-SM3T program are quite good on biology subject.Key Words: Teacher candidates PPG-SM3T program, Scientific attitude of student, Biology subject